INTERA TOMIC POTENTIALS AND THE DIPOLE MOMENT OF THE CADMIUM FORBID DEN (53P2 51So) TRANSITION FOR THE Cd2 SYSTEM (Biological Sciences - PJSIR, 2002)
The molecular  band  appearing  at 6V = 770 cm-1 on the  blue wing of the intercombination  Cd (326.1 nm) line broadened    by  Cd  pressure  has  been   in vestigated.   This  band   was  interpreted   as  a  rain bow  sateJl ite  accompanying  the  dipole 2 forbidden  Cd  (314.1  nm)  line  associated  with  the 53P 51 S transition.  The  profile  of this  band  has  been calculated 0 using the semiclassical model developed by Szudy and Baylis. To obtain this profile the interatomic  potential  of  the molecular  state  lu and  the dipole moment associated  with  this band  have been  modified  to give the best fit profile with   the  experimental  one.